Optimization of the growth conditions for maximum production of the peroxidase by Bacillus subtilis - A. Hassan, Baydaa (Al-Qadisiyah Journal of Pure Science, 2018)
This working was achived in Section of Biology,faculty of Science, Kufa university which contain peroxidase separation and classically of route parameters to work greatest defer of peroxidase through Bacillus subtilis . Fermentation of solid-state of Bacillus subtilis was accepted for improved production of peroxidase using hydrogen peroxide as the substrate of enzyme , greatest activity of the enzyme was achieved in best growth environment , the best conditions were the isolated of Bacillus subtilis from soil and growth in synthetic medium , it gave elevated titer of peroxidase activity , the lactose as carbon source , yeast extract as nitrogen source , after 18 hr of incubation, incubation temperature 30 Â°C and pH = 7 .